THE APPLICATON OF COOPERATIVE LEARNING MODEL TWO STAY TWO STRAY (TSTS) FOR IMPROVING STUDENTS’ APPRECIATION AND CREATION - Titi Sumarni; Johanes Sapri; Alexon Alexon (UNIB Press, 2017)
The purpose of this study is to describe the first application of Two Stay Two Stray learning model can improve the appreciation of learners, the two application of Two Stay Two Stray learning model can improve the students' creativity, and the three effectiveness of the application of Two Stay Two Stray learning model to improve the creation of students. This research uses Classroom Action Research method followed by Quasi Experiment. The data were collected by observation, questionnaire and test. Research Subject Class action is the class XI MIPA students 1. Determination of experimental class and control class by paired, students of class XI MIPA 2 as experimental class and students of class XI MIPA 3 as control class. The results showed that the application of Two Stay Two Stray learning model can improve the appreciation and creation of learners, and the application of Two Stay Two Stray learning model can effectively improve the creation of art and culture in SMA Negeri 1 Seluma. Keywords: cooperative learning model two stay two stray type appreciation, creation